Journey to Bethlehem [videorecording (DVD)] - Anders, Adam; Anders, Nikki; Åström, Peer (Sony Pictures Home Entertainment, 2024)
The live-action Christmas musical adventure for the entire family weaves classic Christmas melodies with humor, faith, and new pop songs in a retelling of the greatest story ever told, the story of Mary and Joseph and the birth of Jesus.